Fragmented Population Structure of Plasmodium falciparum in a Region of Declining Endemicity - Anthony, Thomas G.; Conway, D.J.; Cox-Singh, J.; Asmad, Matusop; Shanmuga, Ratnam; Sunita, Shamsul; Balbir, Singh (The University of Chicago, 2005)
Background. The population genetic structure of Plasmodium falciparum differs between endemic regions, but the characteristics of a population recently fragmented by effective malaria control have been unknown. Methods. Genotypic analysis of 10 microsatellite loci widely separated in the parasite genome was conducted on 288 P. falciparum isolates from 8 foci in Malaysian Borneo, a region in which malaria incidence has been progressively reduced. Results. Within all P. falciparum foci, moderate levels of allelic diversity were found, but levels of multilocus linkage disequilibrium were extremely variable. The population with the highest proportion of mixed-clone infections also had the highest allelic diversity and nonsignificant linkage disequilibrium. In contrast, several populations showed evidence of clonal expansion, and one offshore island population had exceptionally high levels of linkage disequilibrium. Genetic differentiation between many populations was very high and strongly associated with the geographical distance between them. Conclusions. High levels of differentiation and contrasting population structure among P. falciparum populations in Malaysian Borneo indicate that they are genetically independent. This supports the feasibility of individually eradicating the remaining P. falciparum foci.